The Concept of Necessity in International Law and the World Trade Organization : History, Lessons, and Prospects - Andemariam, Senai W., (International Law E-Books Online, Collection 2024., 2024)
Like many concepts in international law, the definition of "necessity" varies widely depending on context. The concepts of necessity in different fields of international law can maintain their unique definitions while learning from each other, and thereby achieve coherence. This book presents the evolution of the concept of necessity, and discusses its definitions in nine different fields of international law. Centering customary international law and the law of the World Trade Organization in his analysis, Dr. Senai W. Andemariam examines the potential for interactions and coherence between concepts of necessity in various fields of international law.